Site-specific interrogation of an ionic chiral fragment during photolysis using an X-ray free-electron laser - Markus Ilchen (Nature Portfolio, 2021)
Ultrashort circularly polarised light pulses from free-electron lasers offer a route for exploring chiral molecules and their dynamics, but remain challenging to harness. Here, X-ray pump-probe experiments enable a site-specific photoelectron circular dichroism measurement on a dissociating chiral molecule.